2016
DOI: 10.4172/2155-9600.1000497
|View full text |Cite
|
Sign up to set email alerts
|

Quinoa (Chenopodium quinoa Willd), from Nutritional Value to Potential Health Benefits: An Integrative Review

Abstract: Chenopodium quinoa Willd, known as quinoa, has been cultivated and consumed by humans for the last 5,000-7,000 years. Quinoa was important to pre-Columbian Andean civilizations, as the Incas considered it a gift from their gods. Quinoa has potential health benefits and exceptional nutritional value: a high concentration of protein (all essential amino acids highly bioavailable), unsaturated fatty acids, a low glycemic index; vitamins, minerals and other beneficial compounds; it is also gluten-free; furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 74 publications
1
23
1
Order By: Relevance
“…Vulgaris ) is a member of the order Caryophyllales. This group comprises angiosperms that emerged early, just after the divergence of monocot and eudicot plants and it includes several crops of great economic importance to the food and energy industries [19,20]. In a previous study, three nsHbs were found in sugar beet, BvHb1.1, BvHb1.2 (class-1), and BvHb2 (class-2).…”
Section: Introductionmentioning
confidence: 99%
“…Vulgaris ) is a member of the order Caryophyllales. This group comprises angiosperms that emerged early, just after the divergence of monocot and eudicot plants and it includes several crops of great economic importance to the food and energy industries [19,20]. In a previous study, three nsHbs were found in sugar beet, BvHb1.1, BvHb1.2 (class-1), and BvHb2 (class-2).…”
Section: Introductionmentioning
confidence: 99%
“…is a pseudo-cereal with attractive nutritional proprieties, and this attribute has greatly increased its consumption in recent years [1]. Quinoa contains unsaturated fatty acids, antioxidants, and essential amino acids, and it is rich in Fe, Mg, fiber, and vitamins while containing high levels of gluten-free protein [2,3]. Because the quinoa plant shows high phenotypic and genetic variability, interest in this crop has also increased globally.…”
Section: Introductionmentioning
confidence: 99%
“…The increased use of marginal soils, such as salt affected lands that are currently not fully utilized, has the potential to contribute to increased yield. Chenopodium quinoa (quinoa) is a favorable candidate for agronomic expansion into these marginal lands and for identification of candidate genes facilitating salinity tolerance because it is naturally adapted to marginal environments (such as the high saline plains in the Andean Altiplano in Bolivia and Peru and the coastal regions of Chile), it is relatively salt tolerant and it produces highly nutritious grains (Hariadi et al, 2011; Gordillo-Bastidas et al, 2016). The potential of this emerging crop was recognized by the United Nations when 2013 was declared the International Year of Quinoa.…”
Section: Introductionmentioning
confidence: 99%